Advanced thermodynamics for engineers - Winterbone, D. E. (Arnold ; John Wiley & Sons, 1997)
Introduces basic concepts that apply over a range of engineering thermodymanics technologies. Considers approaches to cycles, enabling their irreversibility to be taken into account. Gives a detailed study of combustion to show how the chemical energy in a fuel is converted into thermal energy and emissions; analyses fuel cells to provide an understanding of the direct conversion of chemical energy to electrical power; studies property relationships to enable more sophisticated analyses to be made of both high and low temperature plant and irreversible thermodynamics, which contain principles that might hold a key to new ways of efficiently converting energy to power.